Analysis of Main Catch and Bycatch on Catching Devices “Gombang” in Sungai Gayung Kiri Village Rangsang Subdistrict Kepulauan Meranti Regency - Manalu, Irene Natalia; Bustari, Bustari; Zain, Jonny (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
The research was conducted in Sungai Gayung Kiri Village in October 2020. The aim of the study was to identify the composition and proportion of the main, by-catch and discarded catches in gombang fishing gear. The method used in this study is a survey method, namely by interviewing and direct observation in fishing waters, identifying species and counting the number of each species caught by gombang fishing gear. Data analysis used descriptive statistics which were tabulated in the form of tables and graphs. The results showed that pepay shrimp (Sergestes similis) was the main or most dominant catch caught in gombang fishing gear, which was 65.91%. The largest percentage of bycatch is beliak mato (Ilisha elongata) at 0.18%, and the percentage of discharge, namely striped crab (Brachura lannaeus) is 0.04%.